Web-Based Independent Learning Implementation in Universitas Lancang Kuning - Andriani, Refika; Reswita, Reswita; Sri Wahyuni (Jurnal Pendidikan Tambusai, 2024)
Education in the era of revolution of industry 4.0 with the development of Information and Communication Technology (ICT) has various innovations, one of them is the optimal use of the internet in learning activities. This study aims to describe the implementation of web-based independent learning by students of the Education and Vocational Faculty at Lancang Kuning University in the academic year 2022/202. A mixed-method approach was used with a sample of 181 students from the Education and Vocational Faculty in the academic year 2022/2023 which selected by using the random sampling technique. To assess the implementation of web-based independent learning, an online Likert Scale questionnaire was utilized, while interview data was analyzed using qualitative analysis techniques through thematic analysis method. The result indicates that the implementation of web-based independent learning at the Faculty of Education and Vocational of Lancang Kuning University is both effective and efficient. This is supported by the highest average values for each statement selected by students across four different indicators. Web-based independent learning makes the learning process flexible and provides convenience for students in understanding the learning material because students can freely choose their own learning methods.